2014
DOI: 10.1021/jm500571f
|View full text |Cite
|
Sign up to set email alerts
|

Lead Optimization of 1,4-Azaindoles as Antimycobacterial Agents

Abstract: In a previous report, we described the discovery of 1,4-azaindoles, a chemical series with excellent in vitro and in vivo antimycobacterial potency through noncovalent inhibition of decaprenylphosphoryl-β-d-ribose-2'-epimerase (DprE1). Nevertheless, high mouse metabolic turnover and phosphodiesterase 6 (PDE6) off-target activity limited its advancement. Herein, we report lead optimization of this series, culminating in potent, metabolically stable compounds that have a robust pharmacokinetic profile without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 10 publications
(25 reference statements)
1
58
0
Order By: Relevance
“…22 After the incubation, determination of residual enzymatic activity conclusively indicated that, while BTZ043 led to an irreversible inhibition of DprE1, in vitro compound 3 reversibly inhibited the enzyme (Figure 4). Additionally, the MIC value of 3 was determined in the NTB1 strain (Cys387Ser mutation in DprE1) 23,24 that was shown to be resistant to BTZ043. Here also, 3 was found to be an effective inhibitor (Table 1), indicating that it is a reversible and noncovalent inhibitor of DprE1 (see SI).…”
Section: T Uberculosis (Tb) Is a Disease Mainly Caused Bymentioning
confidence: 99%
“…22 After the incubation, determination of residual enzymatic activity conclusively indicated that, while BTZ043 led to an irreversible inhibition of DprE1, in vitro compound 3 reversibly inhibited the enzyme (Figure 4). Additionally, the MIC value of 3 was determined in the NTB1 strain (Cys387Ser mutation in DprE1) 23,24 that was shown to be resistant to BTZ043. Here also, 3 was found to be an effective inhibitor (Table 1), indicating that it is a reversible and noncovalent inhibitor of DprE1 (see SI).…”
Section: T Uberculosis (Tb) Is a Disease Mainly Caused Bymentioning
confidence: 99%
“…To gain bactericidal activity, multiple scaffold morphs were performed. The resulting 1,4-azaindole scaffold underwent several structure– activity relationship (SAR) optimizations to improve bactericidal activity, shift selectivity away from the human phosphodiesterase 6 (PDE6) and increase metabolic stability [40, 41]. PDE6 is a key off target pharmacology for this class as it is expressed in rod and cone photoreceptor cells of the eye, and extended inhibition can be detrimental to visual acuity.…”
Section: Drugs Under Developmentmentioning
confidence: 99%
“…Lead molecules from these optimizations have a marked decrease in PDE6 inhibition (>100 μM) and a good PK profile, while maintaining or improving Mtb activity. This class of DprE1 inhibitors (at 100 mg/kg) had comparable efficacy to INH in a murine model of acute TB infection and to RIF in a chronic model in vivo [41]. An important distinction for this potential drug class is the lack of cross-resistance with the benzothiazones, despite having the same molecular target.…”
Section: Drugs Under Developmentmentioning
confidence: 99%
“…[56][57][58][59][60][61][62] DprE1 is an essential membrane-associated enzyme subunit of the heteromeric decaprenylphosphoryl-b-D-riboseepimerase involved in biosynthesis of D-arabinose, which is a substrate for synthesis of arabinogalactan and lipoarabinomannan. Although the co-crystal structure of DrpE1 with BTZ and TCA1 has been solved and structural basis of compound interaction has been elucidated, 62,63 questions remain why this target is preferred by multiple chemically diverse scaffolds.…”
Section: Multiple Diverse Chemotypes Target Membrane Bound Proteins Imentioning
confidence: 99%